2018
DOI: 10.3390/biomedicines6020039
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Anticancer Agents: Lessons from the Pharmacology of Geniposide and Its Aglycone, Genipin

Abstract: For centuries, plants have been exploited by mankind as sources of numerous cancer chemotherapeutic agents. Good examples of anticancer compounds of clinical significance today include the taxanes (e.g., taxol), vincristine, vinblastine, and the podophyllotoxin analogues that all trace their origin to higher plants. While all these drugs, along with the various other available therapeutic options, brought some relief in cancer management, a real breakthrough or cure has not yet been achieved. This critical rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 194 publications
(250 reference statements)
0
58
0
1
Order By: Relevance
“…In addition, studies have demonstrated the roles of the miR-21/PTEN pathway in tumor growth, migration and invasion (44,45). combined with previous studies regarding the protection of geniposide against tumor (15,46), miR-21/PTEN pathway may contribute to the antitumor effect of geniposide.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, studies have demonstrated the roles of the miR-21/PTEN pathway in tumor growth, migration and invasion (44,45). combined with previous studies regarding the protection of geniposide against tumor (15,46), miR-21/PTEN pathway may contribute to the antitumor effect of geniposide.…”
Section: Discussionmentioning
confidence: 83%
“…Geniposide, a major compound extracted from the gardenia fruit, is a type of traditional chinese medicine for the treatment of inflammation, brain disorders and hepatic disease (11). Geniposide exhibits a broad spectrum of pharmacological actions involving anti-apoptosis (12), anti-inflammatory injury (13), anti-oxidative stress (14), anti-cancer (15) and anti-angiogenesis effects (16). Previous in vitro and in vivo studies have focused on the potential cardioprotective effects of geniposide, particularly in atherosclerosis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,12 ] Geniposide (CAS number: 24512‐63‐8; Figure 1) is the main active ingredient separated and purified from the fruit of Gardenia jasminoides Ellis. [ 13 ] Earlier research reported that geniposide possessed beneficial activities, [ 14 ] such as anti‐inflammation, [ 15 ] antidiabetes, [ 16 ] antiangiogenesis, [ 17 ] antitumor, [ 18 ] and neuroprotection. [ 19 ] For antitumor activity, Qian et al [ 20 ] indicated that geniposide could inhibit cell proliferation and induce cell apoptosis of human oral squamous carcinoma HSC‐3 cells.…”
Section: Introductionmentioning
confidence: 99%
“…A further possible mechanism for the induction of apoptosis was mitochondrial dysfunction and ROS overproduction induced by the zinc chelate of DP1. Induction of ROS overproduction through the mitochondrial respiratory pathways leading to caspases activation and apoptosis appears to be consistent to the anticancer activity of many natural products [58]. The same group also prepared a monodispersed selenium nanoparticle of DP1 that induce apoptosis in HepG2 cells through exactly the same above-mentioned mechanism [40].…”
Section: Anticancer Effectmentioning
confidence: 61%